Cytotoxic and apoptotic-inducing effects of purple rice extracts and chemotherapeutic drugs on human cancer cell lines - Banjerdpongchai R. (2014)
Pigmented rice is mainly black, red, and dark purple, and contains a variety of flavones, tannin, polyphenols, sterols, tocopherols, γ-oryzanols, amino acids, and essential oils. The present study evaluated the cytotoxic effects of purple rice extracts (PREs) combined with chemotherapeutic drugs on human cancer cells and mechanisms of cell death. Methanolic (MeOH) and dichloromethane (DCM) extracts of three cultivars of purple rice in Thailand: Doisaket (DSK), Nan and Payao (PYO), were tested and compared with white rice (KK6). Cytotoxicity was determined by 3-(4, 5-dimethyl)-2, 5-diphenyltetrazolium bromide (MTT) assay in human hepatocellular carcinoma HepG2, prostate cancer LNCaP and murine normal fibroblast NIH3T3 cells. MeOH-PYO-PRE was the most cytotoxic and inhibited HepG2 cell growth more than that of LNCaP cells but was not toxic to NIH3T3 cells. When PREs were combined with paclitaxel or vinblastine, they showed additive cytotoxic effects on HepG2 and LNCaP cells, except for MeOH-PYO-PRE which showed synergistic effects on HepG2 cells when combined with vinblastine. MeOH-PYO-PRE plus vinblastine induced HepG2 cell apoptosis with loss of mitochondrial transmembrane potential (MTP) but no ROS production. MeOH-PYO-PRE-treated HepG2 cells underwent apoptosis via caspase-9 and-3 activation. The level of γ-oryzanol was highest in DCM-PYO-PRE (44.17 mg/g) whereas anthocyanin content was high in MeOH-PYO-PRE (5.80 mg/g). In conclusion, methanolic Payao purple rice extract was mostly toxic to human HepG2 cells and synergistically enhanced the cytotoxicity of vinblastine. Human HepG2 cell apoptosis induced by MeOH-PYO-PRE and vinblastine was mediated through a mitochondrial pathway.